2013
DOI: 10.1097/tp.0b013e31829f162e
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Anemia After Kidney Transplantation Is an Independent Factor for Graft Loss

Abstract: Low Hb levels in the early posttransplantation period (1 month) seem to be an independent prognostic factor for graft loss, but not for mortality, in Spanish RT patients regardless of graft function, recipient and donor characteristics, unfavorable events within the first month, and immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
4
1
1
Order By: Relevance
“…Our anemic patients showed up to a 23 % decrease in the measured GFR at each time point during the 10-year followup, thereby verifying the previous cross-sectional observations on the association between the poor graft function and low Hb levels [1,5,27,39,40]. EPO is the main regulator of erythropoiesis, and anemia may be attributed to insufficient EPO production by the failing graft.…”
Section: Discussionsupporting
confidence: 88%
“…Our anemic patients showed up to a 23 % decrease in the measured GFR at each time point during the 10-year followup, thereby verifying the previous cross-sectional observations on the association between the poor graft function and low Hb levels [1,5,27,39,40]. EPO is the main regulator of erythropoiesis, and anemia may be attributed to insufficient EPO production by the failing graft.…”
Section: Discussionsupporting
confidence: 88%
“…We excluded 3 included studies in the previous meta-analysis due to using the impact of a 1 g/dL increase in hemoglobin level on outcomes. A total of 17 observational studies, 13,58,1322 including 16 463 recipients, finally met the inclusion criteria and were included in the meta-analysis. Figure 1 outlines the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…32 Whereas Pascual et al collected data from recipients in Spain and revealed that the prevalence of anemia after transplantation was 77% at 1 month but decreased quickly within 2 months to 41%, and more slowly later on with prevalence of 16% at 12 months and 14% at 24 months. 21 PTA has multifactorial causes and the onset of anemia can predict the causes. Recipients with early-onset PTA tend to have anemia from iron deficiency due to depletion of iron stores before transplantation, perioperative blood loss, and poor nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Although anemia requiring blood transfusion was more frequent in both groups, it was higher in CDRT patients. Post-transplantation anemia seems to be a risk factor for graft loss, panel reactive antibody of more than 10%, acute rejection episodes [23], and mortality [24].…”
Section: Discussionmentioning
confidence: 99%